2006
DOI: 10.2166/nh.2006.012
|View full text |Cite
|
Sign up to set email alerts
|

Determination and evaluation of some physicochemical parameters in the Dardanelles (Canakkale Strait, Turkey) using multiple probe system and geographic information system

Abstract: The Dardanelles (Canakkale Strait) is a water passage connecting the Aegean Sea and Sea of Marmara. The average depth of the Dardanelles is 60 m; the deepest part reaches more than 100 m. Environmental parameters such as temperature, pH, salinity, dissolved oxygen and total dissolved solids were measured at different depths in the Dardanelles. The sampling period was between December 2002 and March 2003. All the data was measured by a YSI 6600 Model Multiple Probe System. Also, a Geographic Information System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Besides the temporal variations in the nutrient concentrations, especially the southern part of the Dardanelles receives notable nutrient inputs due to domestic wastes from the city of Canakkale and from the rivers such as Saricay and Kalabakli (Polat and Tugrul, 1996;Polat et al, 1998;Turkoglu et al, 2004bTurkoglu et al, , 2004cTurkoglu et al, , 2006Turkoglu, 2008). Therefore, in some periods of this study, extra accumulation of inorganic nutrients was highly pronounced.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Besides the temporal variations in the nutrient concentrations, especially the southern part of the Dardanelles receives notable nutrient inputs due to domestic wastes from the city of Canakkale and from the rivers such as Saricay and Kalabakli (Polat and Tugrul, 1996;Polat et al, 1998;Turkoglu et al, 2004bTurkoglu et al, , 2004cTurkoglu et al, , 2006Turkoglu, 2008). Therefore, in some periods of this study, extra accumulation of inorganic nutrients was highly pronounced.…”
Section: Discussionmentioning
confidence: 68%
“…In a previous study by Turkoglu et al (2006), temperature and salinity measurements showed high variability at the southern part of the Kilitbahir in the Dardanelles. The narrowing of the Dardanelles leads to different temperature and salinity values to the northeast and southwest of the Narrows between Kilitbahir and Canakkale.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The width of the Strait varies from 1.35 to 7.73 km and the narrowest part is located between Canakkale and Kilitbahir. The average depth of the Strait is approximately 60 m, with the deepest part reaching more than 100 m (Unsal et al 2003;Turkoglu et al 2004cTurkoglu et al , 2006Baba et al 2007). However, the depth of the study area in the Dardanelles is 80 m. The location of the sampling station (40809 0 00 00 N 26824 0 00 00 E) is given in Figure 1 Water samples for nutrient analyses were kept frozen until analysis.…”
Section: Methodsmentioning
confidence: 99%